2007
DOI: 10.1021/bi062088k
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Ligand Binding Study of the Third PDZ Domain (PDZ3) from the Mammalian Neuronal Protein PSD-95

Abstract: The thermodynamic parameters associated with the binding of several series of linear peptides to the third PDZ domain (PDZ3) of the postsynaptic density 95 protein (PSD-95) have been measured using isothermal titration calorimetry (ITC). Two strategies were pursued in developing these binding ligands: (1) systematic N-terminal truncation of sequences derived from the C-terminal regions of identified PDZ3-binding proteins (CRIPT, neuroligin-1, and citron) and (2) selective mutation of specific positions within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
143
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(163 citation statements)
references
References 69 publications
20
143
0
Order By: Relevance
“…The weak binding interaction between JAM-A and PDZ3 was not unanticipated and is well within range of binding affinities observed between PDZ3 of MAGUK proteins and their ligands (32,33). The tight junction is a highly dynamic structure (34,35), and it had been demonstrated that there is a high turnover of ZO-1 and of its binding partners like claudin and occludin in stable epithelial monolayers (35,36).…”
Section: ϫ8supporting
confidence: 77%
“…The weak binding interaction between JAM-A and PDZ3 was not unanticipated and is well within range of binding affinities observed between PDZ3 of MAGUK proteins and their ligands (32,33). The tight junction is a highly dynamic structure (34,35), and it had been demonstrated that there is a high turnover of ZO-1 and of its binding partners like claudin and occludin in stable epithelial monolayers (35,36).…”
Section: ϫ8supporting
confidence: 77%
“…15 Their results showed that residues 0 to -5 (See The additional C-terminal extension is not unique for PDZ3. 25,26 In MAGI PDZ1 for example, an extended C-terminal loop makes direct interactions with Arg -4 , Arg -5 and Thr -6 of the peptide ligand and mutation in this C-terminal loop decreases the binding affinity drastically.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 But, since the PDZ domain ligand is often very flexible, it has the possibility to wrap around the surface of the PDZ to make additional favorable interactions outside of the canonical binding groove. This binding groove is typically occupied by only four ligand residues, as defined by hydrogen bonds between backbones of the peptide and the second β-strand of the PDZ domain (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that the partial attenuation of PAR activation by CN2180 is dependent upon the PSD-95/PDZ-binding cyclic peptide KTEV-␤-alanine, we substituted the T and V residues with alanine (KAEA-␤-alanine, CN3200 (Fig. 1), designed to render the myristoylated cyclic peptide ineffective in binding to PSD-95 (30,31). Results show that CN3200 up to 6 nmol had no effect in attenuating NMDA-induced PAR activation (Fig.…”
Section: Polyarginine-linked Tmr-cn2097 and The Myristoylatedlinked Amentioning
confidence: 92%